Literature Review : Analisis Penggunaan Media Canva Untuk Meningkatkan Minat Belajar Siswa : Literature Review : Analisis Penggunaan Media Canva Untuk Meningkatkan Minat Belajar Siswa - Sidauruk, Ernita; Marbun, Deta; Tampubolon, Yohana; Theresa, Theresa; Napitupulu, Even; Manurung, Hisar Marulitua (UNIB Press, 2025)
This study aimed to explore the effectiveness of using Canva application as a learning media in increasing students' interest in learning. Learning media has an important role in creating an interactive and fun learning process, especially in today's digital context. Canva is a web-based graphic design application that provides various features and attractive templates to support learning activities. Through the literature study method, this research examined a number of relevant articles and previous research results regarding the utilization of Canva in the educational environment. The results of the literature review show that the use of Canva as a learning media can provide a more visual, creative, and interesting learning experience for students. The five main articles analyzed showed a significant increase in learning interest after Canva was used in the learning process, both in the form of presentations, infographics, learning videos, and other visual media. In addition to increasing interest in learning, the use of Canva is also proven to make it easier for teachers to develop teaching materials that are more innovative and in accordance with the characteristics of today's students. The use of Canva not only affects the motivational aspect, but also has an impact on better student learning outcomes. Therefore, Canva is recommended as an alternative digital learning media that can create an effective and fun learning atmosphere.